USE OF BIOGRAPHICAL ANALYSIS METHODS IN THE TRAINING OF FUTURE TEACHERS: SCIENTIFIC AND THEORETICAL JUSTIFICATION OF THE PROBLEM - Savchuk, Borys; Kopchuk-Kashetska, Maria; Malona, Svitlana; Bai, Ihor (Mountain School of Ukrainian Carpaty, 2022)
The article updates the problem of using biographical methods in the training of future teachers. The purpose of the research is the theoretical and methodological substantiation of the possibilities of using methods of biographical analysis in the professional and pedagogical training of future teachers to increase their methodological competence. Its solution involved a comprehensive analysis of foreign and domestic experience in the scientific understanding of the problem. The methods of analysis and synthesis, historiographical analysis, monographic analysis, selective analysis, and content analysis were used in the preparation of the research. Based on the results of the analysis of representative foreign and Ukrainian psychological and pedagogical literature, a consolidated position was revealed, according to which biographical analysis methods should focus on the study of a person's mental states, which are the result and consequence of his life path and highlight the features of his social experience. From the point of view of biographical studies, mental states are considered as a special section of the psychological characteristics of an individual, which reflects relatively static and permanent manifestations of his mental experiences at various stages of his life path. This allows us to assert that the methods of biographical analysis have significant potential as a tool for studying the mental states of education seekers and finding out how the behavior and life activities of school students and university students depend on their changes. It was concluded that the conducted research substantiates the effectiveness of using the instrumental capabilities of the methods of biographical analysis in the preparation of future teachers for professional and pedagogical activities. They provide an important key for self-discovery and ordering of her inner world. Therefore, the task of the teacher-biographer is to help the student understand his own life, correct his self-esteem and make his life whole and happy. The prospect of conducting experimental studies, which should verify and confirm the expediency and effectiveness of using methods of biographical analysis in the organization of the educational process, is determined. Keywords: methods of biographical analysis, future teachers, education seekers, mental state, professional and pedagogical training.